Tarih Derslerinde Farklı Becerilere Sahip Öğrencilere Aynı Ders Kitaplarını Sunmak Ne Derece Adildir? : Heinemann Yayınevi Örneği. - KABAPINAR, Yücel (Turkish History Education Journal (TUHED), 2015)
Contemporary approaches in education view students as individuals with different abilities. Instead of classifying and labeling students lazy/hard working, modern educational theories prefer to appreciate them as “less able/more able” by taking into account their skills and motivations. Thus, the question “Do textbooks need to be differentiated for students with different abilities” comes to the mind. The existing situation is to provide the same textbooks to all students even they possess different abilities. Thus, the present study aims to examine and make comparisons basic features of the two different history textbooks called as “core” and “foundation” published by Heinemann Publisher for the same graders with different abilities. Case study among the qualitative research designs was adopted in this study and document analysis method was benefitted since the history textbooks were the study group of the research. Two “core” and two “foundation” history textbooks published by Heinemann were examined in order to determine their basic features and find out their differences. The results of analysis of two types of the history textbooks called as “core” and “foundation” editions revealed that the foundation editions include less number of words and less number sentences as compared to the core counterparts. Similarly, the average number of words in the sentences and the number of abstract concepts were found to be less in foundation history textbooks.